Relationship between social and cognitive functions in people with schizophrenia - Tominaga T (Dove Medical Press, 2018)
Takeo Tominaga,1 Masahito Tomotake,2 Tomoya Takeda,1 Yoshinori Ueoka,3 Tsunehiko Tanaka,4 Shin-ya Watanabe,1 Naomi Kameoka,5 Masahito Nakataki,5 Shusuke Numata,1 Yumiko Izaki,6 Satsuki Sumitani,7 Hiroko Kubo,8 Yasuhiro Kaneda,9 Tetsuro Ohmori1 1Department of Psychiatry, Graduate School of Biomedical Sciences, Tokushima University, Tokushima, Japan; 2Department of Mental Health, Graduate School of Biomedical Sciences, Tokushima University, Tokushima, Japan; 3Field of Psychology, Department of Human Sciences, Graduate School of Technology, Industrial and Social Sciences, Tokushima University, Tokushima, Japan; 4Faculty of Education, Specialized Courses Educational Psychology, Niigata University, Niigata, Japan; 5Department of Psychiatry, Tokushima University Hospital, Tokushima, Japan; 6Health Service and Counseling Center, Tokushima University, Tokushima, Japan; 7Academic Support Office for Students with Special Needs, Tokushima University, Tokushima, Japan; 8Department of Psychiatry, Aizato Hospital, Itano-gun, Tokushima, Japan; 9Department of Psychiatry, Iwaki Clinic, Anan, Tokushima, Japan Purpose: The purpose of the present study was to examine clinical factors related to social function in people with schizophrenia. Patients and methods: The participants were 55 stabilized outpatients with schizophrenia. Their mean age was 39.36 (SD =10.65) years. Social function was assessed using the Quality of Life Scale (QLS). Cognitive function was evaluated with the Measurement and Treatment Research to Improve Cognition in Schizophrenia Consensus Cognitive Battery (MCCB). Clinical symptoms were assessed using the Positive and Negative Syndrome Scale (PANSS), the Calgary Depression Scale for Schizophrenia, and the Drug-Induced Extrapyramidal Symptoms Scale. Results: Neither the MCCB cognitive domain score nor composite score was correlated with the QLS scores. However, of the 10 MCCB subtests, the Trail Making Test Part A and the Brief Assessment of Cognition in Schizophrenia-Symbol Coding (BACS-SC) scores were positively correlated with the QLS scores. Among clinical variables, especially the PANSS negative syndrome scale score had a strong negative correlation with the QLS scores. Stepwise regression analyses showed that the PANSS negative syndrome scale score was an independent predictor of the QLS scores, and although the BACS-SC score predicted the QLS common objects and activities subscale score, the association was not so strong compared to the PANSS negative syndrome scale score. Conclusion: These results indicate that speed of processing evaluated by BACS-SC could predict some aspect of social function but negative symptoms have a much stronger impact on global social function in people with schizophrenia. Keywords: schizophrenia, social function, negative symptom, cognitive function, speed of processing